Effect of disorder on the magnetic properties of LaMn0.5Fe0.5O3 - Bhame, Shekhar D.; Joly, V. L. Joseph; Joy, Pattayil Alias (Physical Review B, 2005)
Polycrystalline LaMn0.5Fe0.5O3 is synthesized by a low-temperature method and the magnetic properties of the resulting powder have been studied after annealing the sample in air at different temperatures in the range 200 degrees C-1350 degrees C. Room temperature Mossbauer spectroscopic studies show that the Fe ions are present in the +3 oxidation state in the material. However, the magnetic properties vary widely in an unexpected manner when samples are annealed at different temperatures. Zero field cooled magnetization studies show a cusp below 100 K, for the sample annealed at 200 degrees C, indicating a spin-glass-like or superparamagnetic behavior. However, this cusp disappears completely when the sample is annealed at 700 degrees C but still showing a magnetic hysteresis loop with reduced magnetization at low temperatures. The cusp again appears when the sample is annealed at higher temperatures with increasing low-temperature magnetization. EPR and IR spectroscopic studies indicate changes in the distribution of Mn3+ and Fe3+ ions in the lattice. The overall results can be explained in terms of random distribution of Mn3+ and Fe3+ ions in the lattice and formation of some magnetic clusters, with the degree of distribution of the ions varying for samples annealed at different temperatures.

Enhanced magnetostrictive properties of Mn substituted cobalt ferrite Co1.2Fe1.8O4 - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of Applied Physics, 2006)
The effect of substitution of Fe and Co by Mn on the magnetostrictive properties of the cobalt ferrite Co1.2Fe1.8O4 has been studied and compared. The studies on Co1.2-xMnxFe1.8O4 and Co1.2Fe1.8-xMnxO4 (0 <= x <= 0.4) showed a marked dependence of magnetostriction on the substitution of both Fe and Co by Mn. Higher magnetostriction is obtained for the substitution of Co by Mn whereas the magnetostriction is reduced substantially on the substitution of Fe by Mn. Higher magnetostriction at low magnetic fields and enhancement of the strain ratio have been observed for the substitution of Co by Mn. (c) 2006 American Institute of Physics.

Tuning of the magnetostrictive properties of CoFe2O4 by Mn substitution for Co - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of Applied Physics, 2006)
Marked changes in the magnetostriction of CoFe2O4 in the substitution of Mn for Co has been observed. The magnetostriction parallel to the applied field direction decreases with increasing Mn content, whereas the magnetostriction perpendicular to the field showed a marked increase for 10% of the Mn substitution. The observed magnetostrictive properties are correlated with the magnetic properties. The results suggest the possibility of tuning the magnetostrictive properties of cobalt ferrite for various applications by proper substitution. (c) 2006 American Institute of Physics.

Effect of sintering conditions and microstructure on the magnetostrictive properties of cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2008)
The effects of sintering temperature and dwell time on the magnetostrictive properties of polycrystalline cobalt ferrite synthesized by the conventional ceramic method have been investigated. The present study showed that the magnitude of magnetostriction strongly depends on the microstructure of the final sintered product. The presence of small and uniform grains with less porous structure in the sintered material leads to enhancement of the magnetostrictive strain. Higher magnetostriction is obtained for samples sintered at a relatively lower temperature of 1100 degrees C. These results are further corroborated by analyzing the effect of some additives during sintering on the microstructural and magnetostrictive properties.

Magnetoelastic properties of terbium substituted cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Chemical Physics Letters, 2017)
The magnetic properties of terbium substituted cobalt ferrites CoFe(2-x)TbxO(4) (x = 0, 0.05, 0.1, 0.15 and 0.2) prepared by conventional solid state method are studied. The coercivity showed marked increase up to x = 0.1 and saturation magnetization decreased with increasing terbium content. Magnetostriction measurements did not show much decrease in the maximum value of strain but significant increase in the slope of magnetostriction was observed for x = 0.15 with moderate magnetostriction of around 144 ppm. The observed magnetic and magnetostrictive properties can be explained on the basis of structural and microstructural changes arising because of terbium substitution. (C) 2017 Elsevier B.V. All rights reserved.

Enhanced strain sensitivity in magnetostrictive spinel ferrite Co1-xZnxFe2O - Bhame, Shekhar D.; Joy, P. A. (Journal of Magnetism and Magnetic Materials, 2018)
We report the magnetic and magnetoelastic properties of spinel oxide system Co1-xZnxFe2O4 (CZF series) where x = 0.0, 0.1, 0.2, 0.3, 0.4, and 0.5. All the composition were prepared by conventional solid state synthesis method and exhibited pure spinel phase formation. The lattice parameters showed gradual increase indicating uniform distribution Zn ions in cobalt ferrite lattice. The magnetic properties such as saturation magnetization and coercive field were drastically affected with Zn substitution showing enhanced saturation magnetization and a sharp decrease in the coercivity. The room temperature magnetostrictive properties showed a promising 30% enhancement in the slope of magnetostriction curve for x = 0.2 composition and a reasonable magnetostrictive strain of 110 ppm indicating its suitability as a promising magnetostrictive material. (c) 2017 Elsevier B.V. All rights reserved.

Magnetic and magnetoelastic properties of Ni-substituted cobalt ferrite - Bhame, Shekhar D.; Shirolkar, Mandar M.; Joy, Pattayil A. (IEEE Magnetics Letters, 2021)
In this letter, magnetic and magnetostriction studies were performed on spinel ferrite Co1-xNixFe2O4 (CNF series) with 0.0 < x < 0.5. All the samples were synthesized by the conventional ceramic method and confirmed to be forming pure spinel phase. The unit cell parameter showed gradual decrease with increasing Ni content. A linear decrease in saturation magnetization (M-s) and coercivity (H-c) was observed with increasing Ni substitution, which could be attributed to reduced magneto-crystalline anisotropy. The room temperature magnetostriction studies revealed a slow decrease in maximum magnetostriction, and interestingly, for 20% reduction of cobalt concentration, i.e., for x = 0.2, a magnetostrictive strain of -164 ppm and substantially high stress sensitivity of -56 x 10(-6) A(-1) m were observed, making Co0.8Ni0.2Fe2O4 suitable for application as a magnetostrictive stress-sensing material.
Keywords: Ferrite; Magnetism in solids; Magnetostriction; oxide; stress sensing